Reconstruction of Islamic Educational Philosophy: Integrating Revelation, Reason, and Experience in Responding to the Challenges of the 21st Century - Toto Ahmad Sahid (International Journal on Education Issues, 2025)
Purpose - This study aims to analyze the urgency of reconstructing Islamic educational philosophy, formulate its core renewal principles, and examine the contributions of classical and contemporary Muslim thinkers in developing an integrative and transformative educational paradigm. Design/Methodology/Approach - The study employs library research as its primary method, drawing on authoritative classical texts and contemporary scholarly works related to Islamic educational philosophy. Data were analyzed through descriptive, thematic, and critical-reflective approaches to identify conceptual patterns and contextual relevance. Findings - The findings reveal that Islamic educational philosophy must shift from a purely normative orientation toward an emancipatory and transformative paradigm grounded in the integration of revelation, reason, and experience. The thoughts of figures such as Al-Ghazali, Ibn Sina, Ibn Khaldun, Syed Muhammad Naquib al-Attas, Fazlur Rahman, and Nurcholish Madjid contribute significantly to strengthening this integrative framework. This reconstruction supports the formation of holistic individuals who possess spiritual depth, intellectual capacity, and social responsibility. Originality/Value - The study implies that reconstructing Islamic educational philosophy is a strategic necessity for developing adaptive educational models capable of addressing global challenges without losing their ethical and spiritual foundations. Further empirical research is recommended to explore practical implementation at various educational levels.